Structural Alterations in the Corpus Callosum Are Associated with Suicidal Behavior in Women with Borderline Personality Disorder - Lischke, Alexander; Domin, Martin; Freyberger, Harald J.; Grabe, Hans J.; Mentel, Renate; Bernheim, Dorothee; Lotze, Martin (Frontiers in Human Neuroscience, 2017)
Structural alterations in the corpus callosum (CC), the major white matter tract connecting functionally related brain regions in the two hemispheres, have been shown to be associated with emotional instability, impulsivity and suicidality in various mental disorders. To explore whether structural alterations of the CC would be similarly associated with emotional instability, impulsivity and suicidality in borderline personality disorder (BPD), we used diffusion tensor imaging to assess the structural integrity of the CC in 21 BPD and 20 healthy control (HC) participants. Our hypothesis-driven analyses revealed a positive correlation between BPD participants’ suicidal behavior and fractional anisotropy (FA) in the splenium and genu of the CC and a negative correlation between BPD participants’ suicidal behavior and mean diffusivity (MD) in the splenium of CC. Our exploratory analyses suggested that suicidal BPD participants showed less FA and more MD in these regions than HC participants but that non-suicidal BPD participants showed similar FA and MD in these regions as HC participants. Taken together, our findings suggest an association between BPD participants’ suicidal behavior and structural alterations in regions of the CC that are connected with brain regions implicated in emotion regulation and impulse control. Structural alterations of the CC may, thus, account for deficits in emotion regulation and impulse control that lead to suicidal behavior in BPD. However, these findings should be considered as preliminary until replicated and extended in future studies that comprise larger samples of suicidal and non-suicidal BPD participants.